The Impact of Disparities in Housing Cluster Development Regulations on Water Catchment Area Protection (Case Study: Bekasi City) - Ramadhan, Genta Aulia; Nursadi, Harsanto (UI Scholars Hub, 2024)
Background: The development of housing clusters in urban areas is usually becoming a significant factor that affecting environmental conditions, especially in terms of protecting water catchment areas. This also happened in Bekasi City, the high demand for housing resulted in a rapid increase in the development of housing clusters which in some cases were not in line with environmental protection regulations. Aims: This study aims to analyze the impact of regulatory gaps related to spatial planning and environmental management on the protection of water catchment areas in Bekasi City. Methods: Using a case study approach, this study analyzes existing policies, their implementation in the field, and the impact of these gaps on the function of water catchment areas. Results: The results of the study indicate that regulatory gaps and weak supervision contribute to the reduction of water catchment areas, increased flood risk, and decreased environmental quality in the Bekasi City area. Conclusion: The recommendations of this study include increasing regulatory strictness, improving the supervision system, and adjusting spatial planning policies to focus more on the balance of development and environmental sustainability.